The Human Drift - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Human Drift" by Jack London is a philosophical treatise that reflects on human migration and survival, likely written in the early 20th century. The work explores the historical patterns of human movement driven by the primal need for sustenance, touching on themes of civilization's rise and fall while critiquing the destructive nature of humanity. The opening of the book establishes a narrative framework that examines the instinctual drives behind human migration, comparing these movements to that of animals in search of food. London emphasizes that migration has been a defining characteristic of human evolution and societal development, resulting in the conquest and displacement of weaker groups. He outlines various historical migrations, illustrating that the quest for food and survival underlies much of humanity's violent history. The passage vividly portrays the struggle for existence and suggests that such patterns persist in modern society, hinting at the recurring cycles of population growth and societal conflict that define human history. (This is an automatically generated summary.)
The Human Drift -- Small-Boat Sailing -- Four Horses and a Sailor -- Nothing that Ever Came to Anything -- That Dead Men Rise up Never -- A Classic of the Sea -- A Wicked Woman (Curtain Raiser) -- The Birth Mark (Sketch)
Release date is 1999-03-01
Transcribed from the 1919 Mills and Boon edition by David Price
Keywords: American drama -- 20th century; American essays -- 20th century